Pengaruh Kualitas Pelayanan dan Store atmosphere terhadap Keputusan Pembelian Konsumen Jaya Fried Chicken di Singaraja - Putu Evi Yuliantini; I Wayan Suwendra (Universitas Pendidikan Ganesha, 2025)
This study aims to determine the effect of service quality on purchasing decisions, determine the effect of store atmosphere on purchasing decisions, and determine the effect of service quality and store atmosphere simultaneously on consumer purchasing decisions. This study uses a quantitative method with data collection techniques through interviews and distributing questionnaires to 140 respondents who are JFC consumers in Singaraja. This study uses multiple linear regression data analysis. The hypothesis tests used are t-test, F-test, and coefficient of determination test processed using SPSS version 25 which shows that service quality partially has a positive and significant effect on purchasing decisions, store atmosphere partially has a positive and significant effect on purchasing decisions, and simultaneously the variables of service quality and store atmosphere have a positive and significant effect on consumer purchasing decisions. Overall, the variables of service quality and store atmosphere contribute to purchasing decisions by 41.9% and the remaining 58.1% is influenced by other variables not studied.